Effect of Education Level and Employee Work Performance Appraisal on Career Development in the Office PDAM Padang City - Aldino, Helmi Prilla; Susanti, Yona Windra (Bina Bangsa International Journal of Business and Management, 2022)
This study aims to determine the effect of education level and work performance assessment on the career development of PDAM Padang City employees. This research is in the form of quantitative research using primary data obtained from distributing questionnaires. The research population includes employees at PDAM Padang. The research sample data were 91 respondents. The data analysis method used was multiple linear regression. The results of this study indicate that the level of education has a positive and significant effect on career development and job performance appraisal has a positive and significant effect on career development